METODE YANBU’A DALAM PENINGKATAN KEMAMPUAN MEMBACA AL-QUR’AN DI PESANTREN JOMBANG - Ainiyah, Qurrotul; Miftahul Himmah, Siti (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2023)
The Yanbu'a method is a method of reading, writing and memorizing, to read it students are not allowed to spell, read it quickly, remain fluent, and do not break and adapt it to the rules of makhrijul letters. The ability to read the Koran properly is in accordance with the Shari'a/rules explained by the science of recitation. This research method uses a qualitative research method with a qualitative descriptive research design. The results of field research show that: 1) The ability to read the Qur'an of students at the Fathul Ulum Jombang Islamic Boarding School has increased in several indicators of the ability to read the Koran, including: a) Fluency in reading the Koran b) Accuracy Tajweed c) Accuracy of Makhraj. 2) The application of the Yanbu'a Method at the Fathul Ulum Jombang Islamic Boarding School has 3 stages, namely: a) the planning stage: conducting teacher training, preparing the Yanbu'a Method book, the Koran with Rosm Ustmani . b) stages of implementation: greetings, reading chadharah (tawasul), do'adsb. Submission of material by way of deliberation, repetition and soroga. c) evaluation stages: daily/semester evaluation and volume final evaluation.